Integrasi Konsep Keislaman Yang Rahmatan Lil ‘Alamin Menangkal Faham Ekstremisme Sebagai Ideologi Beragama Dalam Bingkai Aktifitas Kegiatan Keagmaan Mahasiswa Di Kampus Universitas Bondowoso - Hosaini (Fakultas Agama Islam, 2017)
Islamic comes from arabic word of aslama, yuslimu islaman. And this word has meaning (salvation/save) that a characterictics of islamic teachings for islamic people around the word. and islam as a savior of life. From various problems that can damage the existence of his people In this study used a qualitative approach. It said gualitatifve because it has the following characterictics nature background, human as instrument, a gualitatifve method, inductive data analysis, based on theory, discriptive it determine the process more important rather than the result. The are limits set by focus, specific criteria for data validity, designs are temporar, research results are negotiated and mutually agreed upon. The cause of the emergence of fanaticims in Unibo students is based on the lack of islamic education, the scope of concepts or theories about the nature of islamic education it still needs to be increased in accordance with the principles of religious dogmatism based on the Qur’an and Hadits